Longitudinal cumulative outcome after adult spinal deformity surgery - Susanna Hiltunen; Jussi P. Repo; Liisa Pekkanen; Hannu Kautiainen; Kati Kyrölä (BMC Musculoskeletal Disorders)
Abstract Backgrounds The primary aim of this study was to investigate how the level of disability, pain, and health-related quality of life (HRQL) change during comprehensive longitudinal follow-up period after adult spinal deformity (ASD) surgery. A secondary aim was to evaluate the prevalence and time of revision surgeries due to mechanical complications. Methods Altogether 138 ASD patients were operated at Central Finland Central Hospital between 2007 and 2019. Patients’ HRQL was followed up with the following patient-reported outcome questionnaires; the Oswestry Disability Index (ODI), the Pain Visual Analogue Scale (Pain-VAS) and the Scoliosis Research Society questionnaire version 30 (SRS-30). The operation criterion was severe symptomatic sagittal and/ or coronal spinal deformity. Results Altogether, 128 patients were included. The ODI (p < 0.001), the leg Pain-VAS (p < 0.001), and the back Pain-VAS (p < 0.001) continued to improve up to five to seven years after ASD surgery. The achieved level remained significant at follow-up (p < 0.001). The improvement that was achieved in the first year in the SRS-30 domains did not deteriorate notably at longitudinal follow-up. Ten years cumulative prevalence of mechanical failure after surgery was 24% (95% CI: 12–44%). Conclusions Patient-reported outcomes improve up to five to seven years after ASD surgery and seemed to remain significantly better than preoperative scores at longitudinal follow-up. The majority of the mechanical complications cumulated over the first two years of follow-up.